On the Issue of Responsibility of Teens Boarding Schools - Anzhelika Tolkachova (Pedagogical Discourse, 2015)
Pedagogical aspects of education responsibility in young adults schools are studied in the article. The positions of domestic and foreign researchers on the merits of responsibility as a pedagogical problem have been offered. Some approaches to the concept of responsibility, namely the characteristic of property of the entity that is interconnected with autonomy, initiative, diligence and other qualities have been singled out; ability of the individual to determine their duties and carry them, to carry out self-assessment and monitoring their implementation; a certain level of moral development of the individual; focus on the moral development of the individual. Classification of adolescents enrolled in secondary boarding schools, such as: orphans; children taken from their parents by the court; children whose parents are deprived of parental rights or convicted under arrest during the investigation, found incompetent to be on long-term care, as well as parents, the seat of which is unknown, or that otherwise do not participate in the maintenance and education of their children; thrown and street children who have no idea of ​​responsibility.